Visual preference of pedestrians’ wayfinding signages: A systematic literature review - Zhou, Jialu; Ujang, Norsidah; Abdul Aziz, Faziawati; Abd Manan, Mohd Shahrudin (Universiti Putra Malaysia, 2024)
Urban spaces are often crowded and complex, posing a significant challenge for pedestrians navigating a city. Enhancing walking facilities requires a comprehensive understanding of pedestrians' visual preference for wayfinding signage and the evaluation methods applied. This paper presents a systematic review of 80 studies using the PRISMA methodology, delving into the philosophical background, benefits, evaluation methods, and influencing factors related to wayfinding signage visual preference while identifying existing research gaps. The results underscore the substantial influence of wayfinding signage visual preference by both its physical characteristics and aesthetic perception. These findings lay the foundation for a comprehensive research framework for assessing visual preference. This study suggests that urban wayfinding signage design should intricately consider the interplay between signage’s physical characteristics and aesthetic perception, integrate spatial function and visual effect, balance personalised and standardised needs, and improve signage function and aesthetic quality. The findings fill a critical gap in the existing literature about the visual preference of wayfinding signages and offer valuable insights and guidance for future research endeavours.